Building Research Capacity in HIV and Noncommunicable Diseases in Africa: A Mentorship and Leadership Workshop Report. Issue 1 (27th August 2022) - Aliyu, Muktar H.; Sani, Mahmoud U.; Ingles, Donna J.; Tsiga-Ahmed, Fatimah I.; Musa, Baba M.; Ahonkhai, Aimalohi A.; Salihu, Hamisu M.; Audet, Carolyn M.; Wester, C. William
Abstract : Introduction: Few structured mentoring programs target early-stage investigators in Africa, creating a gap in mentorship skills where HIV burden is greatest. We describe findings from a Nigeria-based workshop for early-career physician scientists to build mentoring and leadership capacity in HIV and noncommunicable disease research. Methods: Baseline surveys captured participant demographics, confidence in implementing mentoring competencies, and perceived importance of workshop training domains. The workshop included didactic presentations, small group activities, and interactive discussions. Daily surveys evaluated sessions, and postworkshop surveys solicited overall course impressions. Results: Of the 33 participants, most were male (n = 21, 63.6%) and from medicine, laboratory sciences, and surgical specialties. "Building mentees' confidence" and "setting mentees' research goals" were ranked as areas where participants most believed they needed training. Sessions were rated favorably across five areas. Greatest improvements in mean scores were for confidence in identifying personal temperament styles, describing mentoring and leadership theories/frameworks, and developing mentoring plans. Additional identified workshop strengths were content relevance, leadership case series, interactive nature, and collegial atmosphere. All respondents indicated learning something new/useful/helpful in each session. At 6-month postworkshop, most respondents (25 of 26, 96%) had replicated or plan to replicate parts of the workshop in their departments/institutions. Discussion: Effective mentoring training initiatives targeting future academic leaders have the potential to create skilled academicians who can impart mentoring skills and competencies to their mentees.